Tourists’ Attitude towards the Purchase of Thangka Paintings (Nepalese Journal of Hospitality and Tourism Management, 2021)
Thangka painting is an important handicraft product, which has its importance and features. The root of the painting lies in Buddhism where the painting holds great importance. The current research has explored the factor influencing tourist attitudes towards purchase of thangka paintings. The study used a quantitative research method with a descriptive and explanatory research design. The convenience sampling technique was used where the primary data was collected through a structured questionnaire. The international tourists who purchased thangka paintings in the Thamel and Bouddha area were studied and a total of 156 questionnaires were collected and analysed using a statistical tool such as correlation and regression. The finding revealed that there is a significant and positive relationship between the factors. The result further revealed that product oriented shopping, and process orientation shopping has a significant impact towards the attitude to purchase of thangka.